The politics of trauma and reconciliation - Humphrey Michael (Temida)
This paper explores transitional justice as a way to bring an end to violence and consolidate peace. It approaches transitional justice as an expression of the 'never again' consensus to prevent or prosecute crimes against humanity. It explores transitional justice as an expression of globalizing law and the implications this has for the recovery of the 'rule of law' and 'political legitimacy' in the post conflict State. It takes Robert Meister (2002)'s formulation of the politics of victimhood, revenge and resentment in the relationship between the beneficiaries and the victims of injustice, as remaining at the centre of transitional justice politics in trying to decide on the balance between reconciliation and justice projects. It explores how human rights discourse has been used to de-politicise the 'victim' by adopting an individually embodied concept of violence as opposed to a structural one. It argues that transitional justice as an expression of globalizing law has been primarily directed at maintaining peace to achieve closure on past 'evil' but that the beneficiary-victim issue has re-emerged in the social justice movements and renewed desire for prosecutions.